Cyclic variation analysis of palm biodiesel fuel in low compression marine diesel engine - Che Wan Mohd Noor, Che Wan Othman; R., Mamat; Ali, Obed; Najafi, G.; Wan Nur Diyana, Mansor (Akademi Baru, 2020)
Environmental pollution due to fossil fuel combustion has made biodiesel a viable option. Biodiesel fuel has been widely used in land-based vehicle engines, but it is limited to marine sectors. This study investigated the cyclic variations effect of palm biodiesel to determine combustion stability in low compression marine diesel engine. The time series of peak pressure and indicated mean effective pressure is examined using statistical and continuous wavelet transformation methods. The results show that the cyclic variations on marine engine operated with palm biodiesel are better than diesel, as indicated by lower COVpmax and COVIMEP values, which are below 1.29% and 2.50% respectively. Increase the percentage of palm biodiesel in blends has gradually reduced the COVIMEP and the B30 palm biodiesel blend produces the minimum cyclic variations of IMEP with 1.91%. This finding was agreed with the wavelet spectrum results which revealed that the B30 palm biodiesel blend has the lowest IMEP frequency oscillation. The B30 palm biodiesel blend has produced the most stable combustion among the tested fuels.